Analisis Break-Event-Point dalam Penentuan Target Laba Produksi pada Usaha Kue Bapilin Dua Saudara - Rahmi, Mega; Syafni, Bintang; Wulandari, Desi; Valencia, Dheva; Maulana, Vickry Adha Yurdeka; Putra, Yosep Eka (Journal of Economics and Management, 2024)
This research explores the application of Break-Even-Point (BEP) analysis in setting financial strategies for small businesses, specifically the Bapilin Dua Saudara cake business. Using the Cost-Volume-Profit (CVP) approach, this study aims to determine the break-even point as well as the profit target that can be achieved through optimizing production volume, managing costs, and setting selling prices. Data was collected through interviews, observations, and documentation studies to ensure a comprehensive analysis. The results show that the utilization of BEP analysis allows entrepreneurs to understand the interrelationship between cost and revenue elements, so that they can design production strategies that are efficient and adaptive to market dynamics. This research confirms the importance of BEP-based financial analysis as a strategic profit planning tool to support small business sustainability and growth.